Investigação de mutações nos genes sinápticos SHANK2 e SHANK3 em Transtornos do Espectro do Autismo - Rosan, Dante Bruno Avanso [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Autism Spectrum Disorders (ASD) are complex neuropsychiatric diseases, with widely etiology and clinical manifestations. Such manifestations are observed before three years of life. The prevalence is high in the population, with a ratio of four affected men for each affected woman. In only 10-25% of cases an etiological factor is observed, genetic or environmental, depending of the composition of samples and laboratory techniques used. There are descriptions of hundreds of genes and genomic regions associated with predisposition, they present mutations and copy number variations (CNVs) and most have expression in the central nervous system, especially at synapses. Among the candidate genes, we highlight the SHANK2 and the SHANK3, not yet studied in Brazilian subjects. In SHANK2, located in 11q13.2, mutations have been described in seven of its 25 exons, while in SHANK3 located at 22q13 with 23 exons, there are descriptions of mutations in several exons, but especially three. Many mutations in these two genes were observed in autistic patients, but not in healthy controls, suggesting an involvement in the etiology of the disease. This study investigated mutations in exons 11, 13 and 22 of SHANK2 gene and exons 2, 6 and 22 of SHANK3, which are most often involved in ASD findings. The study of six exons was performed by direct sequencing, in 200 affected and the results were compared to a genome bank with 566 healthy controls. Eleven alterations were found, six on SHANK2 gene, one not yet described, and five in SHANK3 gene, all not previously described. No patient had more than one alteration in SHANK2 or SHANK3, or both genes. The results showed that mutations in SHANK2 and SHANK3 gene are frequent in the Brazilian population with ASD and are related to the etiology of these diseases. However, the clinical relevance of each of the alterations found should be investigated. This study may help...

Os Transtornos do Espectro do Autismo (TEA) são doenças neuropsiquiátricas complexas, com etiologia e manifestações clínicas muito variáveis. Tais manifestações são observadas antes dos três anos de vida. A prevalência é alta na população, com uma proporção de quatro homens afetados para cada mulher afetada. Em apenas 10-25% dos casos um fator etiológico é observado, genético ou ambiental, dependendo da composição da casuística e das técnicas laboratoriais utilizadas. Há descrições de centenas de genes e regiões genômicas associadas com a predisposição, por apresentarem mutações e variações no número de cópias (CNVs) e a maior parte tem expressão no sistema nervoso central, principalmente em sinapses. Entre os genes candidatos, se destacam o SHANK2 e o SHANK3, ainda não estudados em casuísticas brasileiras. No SHANK2, localizado em 11q13.2, já foram descritas mutações em sete de seus 25 éxons, enquanto no SHANK3, localizado em 22q13 e com 23 éxons, também há descrições de mutações em vários éxons, mas especialmente em três. Muitas mutações nestes dois genes foram observadas em autistas, mas não em indivíduos controles, o que sugere seu envolvimento na etiologia da doença. Este estudo investigou mutações nos éxons 11, 13 e 22 do gene SHANK2 e nos éxons 2, 6 e 22 do SHANK3, que são os mais frequentemente envolvidos nos achados em TEA. O estudo dos seis éxons foi realizado por sequenciamento direto, em 200 afetados e os resultados foram comparados a um banco de dados com os de 566 controles saudáveis. Onze alterações, seis no gene SHANK2, uma delas ainda não descrita, e cinco no gene SHANK3, todas não descritas anteriormente. Nenhum paciente apresentou mais de uma alteração em SHANK2 ou SHANK3, ou nos dois genes. Os resultados mostraram que mutações nos genes SHANK2 e SHANK3 são frequentes na população brasileira com TEA e estão relacionadas com a etiologia destas doenças...
Keywords: Genética humana; Autismo; Sinapse; Família SHANK